Phosphate Modified Screen Printed Electrodes by LIFT Treatment for Glucose Detection - Francesco Milano; Livia Giotta; Daniela Chirizzi; Simos Papazoglou; Christina Kryou; Annarita De Bartolomeo; Vincenzo De Leo; Maria Rachele Guascito; Ioanna Zergioti (Biosensors, 2018)
The design of new materials as active layers is important for electrochemical sensor and biosensor development. Among the techniques for the modification and functionalization of electrodes, the laser induced forward transfer (LIFT) has emerged as a powerful physisorption method for the deposition of various materials (even labile materials like enzymes) that results in intimate and stable contact with target surface. In this work, Pt, Au, and glassy carbon screen printed electrodes (SPEs) treated by LIFT with phosphate buffer have been characterized by scanning electron microscopy and atomic force microscopy to reveal a flattening effect of all surfaces. The electrochemical characterization by cyclic voltammetry shows significant differences depending on the electrode material. The electroactivity of Au is reduced while that of glassy carbon and Pt is greatly enhanced. In particular, the electrochemical behavior of a phosphate LIFT treated Pt showed a marked enrichment of hydrogen adsorbed layer, suggesting an elevated electrocatalytic activity towards glucose oxidation. When Pt electrodes modified in this way were used as an effective glucose sensor, a 1–10 mM linear response and a 10 µM detection limit were obtained. A possible role of phosphate that was securely immobilized on a Pt surface, as evidenced by XPS analysis, enhancing the glucose electrooxidation is discussed.